The influence of Work Environment on the Performance of Civil service Police Unit and Fire Dapartement Employees in Sidenreng Rappang - Dian Faradillah Hamka; Fadlina Fadlina; Mifta Farid Salam (Paser Institute Management and Busines, 2024)
This study aimad to determine the influence of the work environment on the perfomance of employees Civil Service Police Unit and Fir Dapartment of Sidenreng Rappang regency. The population in this study amounts to 318 employees, and the respondents wev 50 civilservans (ASN), selected using a non-probability sampling techniques, namely purposive sampling. Data was collected from both primary and secondary source. The data collection merhods used include observation, interviews, questionnaires, and documentation. The method employed in this research was a descriptive quantitative method. Based on the analysis, it was found that the work enviroment variable had a positive and significant influence on the performance of employees at the Civil Service Police Unit and Fire Dapartment in Sidenreng Rappang Regency, as indicated a t-value (5.432) greater that the t-table (2.013). therefore, the hypothesis stated that the work environment influences employees performance can be accepted. The coefficient of determination (R Square) indicates that the work environment variable explains 38.9% of the variation in employee performance, while the remaining 61.1% is influenced by other factors beyond the variables in this study. Keywords : Work environment, employee performance.